Analisis Intensi Konsumsi Tablet FE Pada Ibu Hamil di Puskesmas Metro Kota Metro Provinsi Lampung - Tri Ayati; Dessy Hermawan; Christin Angelina (Malahayati Nursing Journal, 2024)
ABSTRACT During pregnancy, iron requirements increase by 25% compared to non-pregnant women. Anemia in pregnancy is a risk factor for poor birth outcomes. Adequate iron supplementation in pregnancy is currently the most common and appropriate strategy for controlling iron deficiency anemia during pregnancy. The success of iron supplementation depends on whether pregnant women adhere to taking Fe tablets or not. Compliance in consuming TTD is a form of behavior so that the tendency to comply with regular TTD consumption can be analyzed using behavioral theory. One of the behavioral theories that can be used is the Theory of Planned Behavior (TPB). Based on the background above, researchers are interested in conducting an analysis of pregnant women's intentions to consume Fe tablets, especially at the Kota Metro Health Center. The type of research used in this research is quantitative analysis with a cross sectional design. The sample used in this research was 89 pregnant women in the working area of the Kota Metro Health Center. Data analysis used the Chi-Square test and multivariate binary logistic regression analysis. The results of Chi Square analysis show that there is a significant relationship between behavioral intention and attitude toward behavior (p-value=0.003; OR=3.696; 95% CI=1.521 - 8.981), subjective norm (p-value=0.000; OR=4.889; 95 % CI= 1.947-12.271), and perceived behavioral control was (p-value=0.001; OR=4.978; 95% CI=1.952 - 12.692). The results of the binary logistic regression analysis show that the attitude towards the behavior variable has a significant effect on the behavioral intention variable (P=0.0110.05 with an Exp(B) value of 3.655). The attitude towards the behavior has a significant effect on the behavioral intention of Ferrous Sulfat consumption in Pregnant Women in Kota Metro Health Center. Keywords: Ferrous Sulfat Tablets, Pregnant Women, Theory of Planned Behavior ABSTRAK Pada saat hamil, kebutuhan zat besi meningkat 25% dibandingkan ibu tidak hamil. Anemia pada kehamilan memiliki faktor risiko untuk terjadinya hasil luaran persalinan yang buruk. Kecukupan suplementasi zat besi dalam kehamilan saat ini merupakan strategi yang paling umum dan tepat untuk mengendalikan anemia defisiensi besi selama kehamilan. Keberhasilan suplementasi zat besi bergantung pada patuh tidaknya ibu hamil dalam mengkonsumsi tablet Fe. Kepatuhan dalam mengkonsumsi Tablet Tambah Darah (TTD) merupakan suatu bentuk perilaku sehingga kecenderungan untuk patuh dalam konsumsi TTD secara teratur dapat dianalisis menggunakan teori perilaku. Teori perilaku yang dapat digunakan salah satunya adalah Theory of Planned Behavior (TPB). Berdasarkan latar belakang di atas, peneliti tertarik untuk melakukan analisis mengenai intensi ibu hamil dalam mengkonsumsi tablet Fe khususnya di Puskesmas Metro Kota Metro. Jenis penelitian yang digunakan dalam penelitian ini adalah kuantitatif analisis dengan desain cross sectional. Sampel yang digunakan pada penelitian ini adalah ibu hamil di wilayah kerja Puskesmas Metro Kota Metro sebanyak 89 orang. Analisa data menggunakan uji Chi-Square dan analisis multivariat regresi logistik biner. Hasil analisis Chi Square menunjukkan adanya hubungan yang signifikan antara behavioral intention dengan attitude toward behavior (p-value=0,003; OR=3,696; 95% CI=1,521 - 8,981), subjective norm (p-value=0,000; OR=4,889; 95% CI= 1,947-12,271), dan perceived behavioral control sebesar (p-value=0,001; OR=4,978; 95% CI=1,952 - 12,692). Hasil analisis regresi logistik biner menunjukkan variabel attitude towards the behavior signifikan berpengaruh terhadap variabel behavioral intention (P=0,011 0,05 dengan nilai Exp(B) 3,655). Attitude towards the behavior merupakan faktor yang paling mempengaruhi niat ibu hamil dalam mengkonsumsi TTD. Kata Kunci: Tablet Tambah Darah, Ibu Hamil, Theory Planned Behavior